Evaluation of Skin and Soft Tissue Infection Outcomes and Admission Decisions in Emergency Department Patients - Nicholas Black; Jon W. Schrock (Emergency Medicine International)
Background. Skin and soft tissue infections are common presenting complaints for Emergency Department (ED) patients. Although they are common, there remain no definitive guidelines on decisions of admission for these patients. Objectives. To determine the influence of demographic and clinical information of those presenting with skin and soft tissue infection(s) (SSTI) on both disposition and treatment failure. Methods. We prospectively enrolled adults with SSTI seen at a large urban ED. Secondary outcome was treatment failure. Statistics utilized t-tests and multivariate logistic regression. Results. We enrolled 125 subjects and 32 were admitted. 15.2% of patients failed treatment with both increasing age and infection area correlating with admission. IV drug use (IVDU) (OR: 10.2; 95% confidence interval [CI]: 1.9 to 50.0) and recent antibiotic use (OR: 2.9; 95% CI 1.003 to 8.333) independently predicted admission. Age and recent surgery in the area of infection (OR: 6.4; 95% CI 1.3 to 30.8) showed positive association with treatment failure. IV antibiotics (OR: 22.3; 95% CI 2.8 to 179.4) and admission (OR: 12.1; 95% CI 2.9 to 50.4) strongly predicted treatment failure. Conclusions. Age, infection size, IVDU, and recent antibiotics predicted admission. Age, recent surgery at infection site, IV antibiotics, and admission correlated with treatment failure.